SYMPTOMATIC CRITERIA FOR BRONCHIAL ASTHMA AND CHRONIC OBSTRUCTIVE PULMONARY DISEASE OVERLAP SYNDROME - Nasirova Aziza Akbarovna (Scholar Express Journals, 2023)
Coexisting forms of these pathologies are often the result of the simultaneous manifestation of a number of risk components, with tobacco use, untreated AD, and recurrent respiratory infections considered to be the leading ones. In this aspect, the formation of each individual component depends on the patient's genome.
Keywords: Bronchial asthma crossing syndrome; chronic obstructive pulmonary disease